Human Nutrition - Kainoa Fialkowski Revilla, Marie; Titchenal, Alan; Draper, Jennifer (Open textbook library., 2020)
This textbook serves as an introduction to nutrition for undergraduate students and is the OER textbook for the FSHN 185 The Science of Human Nutrition course at the University of Hawai'i at Mānoa. The book covers basic concepts in human nutrition, key information about essential nutrients, basic nutritional assessment, and nutrition across the lifespan.